علاقة الرضا الوظيفي بالروح المعنوية لدى مديري المدارس الابتدائية المتربصين - معوش, عبد الحميد; صرداوي, نزيم (جامعة الوادي University of Eloued, 2017)
هدفت هذه الدراسة معرفة علاقة الرضا الوظيفي بالروح المعنوية لدى مديري المدارس الابتدائية المتربصين بولاية المسيلة، كما هدفت أيضا التعرف على مستوى الرضا الوظيفي والروح المعنوية لدى أفراد العينة والفروق ذات دلالة إحصائية عند مستوى (α = 0,05) في درجة الرضا الوظيفي والروح المعنوية باختلاف متغيرات الدراسة (العمر، المؤهل العلمي، الخبرة في التعليم). وقد أجريت الدراسة على عينة قوامها (52) من مجموع مديري المدارس الابتدائية المتربصين بولاية المسيلة، والبالغ عددهم (115) مديرا للعام الدراسي 2015/2016. أي بنسبة (45,21 %) وخلصت الدراسة إلى النتائج الآتية: أن مستوى الرضا الوظيفي والروح المعنوية لدى المديرين المتربصين كان بدرجة مرتفعة، وإلى وجود فروق ذات دلالة إحصائية بينهم تبعًا لمتغير (العمر) لصالح الفئة العمرية (46 سنة فما فوق) وعدم وجود فروق تبعًا لمتغيري (متغير المؤهل العلمي، الخبرة في التعليم)، وقدمت الدراسة عددًا من المقترحات المرتبطة بنتائجها. This study aimed to identify the relationship of job satisfaction For moral spirit For primary director's headmasters of M'sila province It also aims to Know the elements of The level of the functional satisfaction and moral spirit For the elements of the sample Is there differences of statistic sign at the level of (a = 0,05) In the degree of functional satisfaction and moral spirit according to variables of the study(age, scientific qualifications, teaching experience) The study has already made an sample of (52) elements of the total of the trainee primary school directors from M'sila province. they are estimated at (115) school directors for the academic year 2015/2016; ie at the average of (45,21 %) .the study concludes to the following results: the level of the functional satisfaction and the moral spirit for the trainee school directors was with the high degree and it alludes to the differences of statistic sign ,according to variables of the age in favour of given category of people (aged of 46 years old and more) and it demonstrates the no _existence of differences according to both of the two variables (scientific qualifications and longevity of teaching), The study offers many of suggestions related to its result
دراسة ميدانية بولاية المسيلة
مقال
Keywords: الرضا الوظيفي؛ الروح المعنوية؛ المدير المتربص; job satisfaction, morale, Director Apprentice